Korupsi dan Pertumbuhan Ekonomi - Syadilla Dharayu Marista; Alfa Farah (Diponegoro Journal of Economics, 2024)
The influence of corruption and economic growth remains a subject of debate. Generally, this study aims to empirically analyze the relationship between corruption and economic growth in 125 countries worldwide during the 2016-2019 period. Using the Fixed Effect Model (FEM) estimation method, the results show that the corruption variable has a positive but not significant impact on economic growth.